NO and NO2 as non-innocent ligands: A comparison - Kaim, Wolfgang; Das, Atanu; Fiedler, Jan; Záliš, Stanislav; Sarkar, Biprajit (Coordination chemistry reviews, 2020)
•Redox systems (NO)n and (NO2)n are presented to reveal parallels and differences.•The suitability of (NO)n and (NO2)n for metal coordination is contrasted.•The scarcity of metal complexes with (NO2)n ligands (n = 0,+) is discussed.•Strategies to stabilize an NO2 ligand are pointed out.•The systems O-NOn and M-NOn are compared. The potential of environmentally and technically relevant NO2 for non-innocent ligand behavior in coordination compounds is being evaluated in comparison with the well-studied metal complexes of nitrosyl, NOn (n = +,0,-,2-). A ruthenium semiquinone (Q−) radical complex platform [Ru(Q)(L)(NOx)] (x = 1 or 2, L = mer tridentate ligand) can serve to contrast the ligand characteristics of (NO)n and (NO2)n. Strategies to stabilize metal coordinated nitrogen dioxide (as “nitro” ligand NO2) versus the well established nitrite NO2− are suggested.